The Governor's Role in Policy Evaluation in the Preparation of the Banten Province RKPD - Heru Wahyudi; Jaka Maulana; Angga Rosidin (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to examine the role of policy evaluation in the preparation of the Regional Government Work Plan (RKPD), with a focus on the integration of performance monitoring and assessment results into annual development planning. This study uses a literature review approach to analyze various theories of policy evaluation, regional planning systems, and institutional dynamics that influence the utilization of evaluation results at the regional government level, particularly in Banten Province. The results show that evaluation models such as CIPP, objective-based evaluation, and utilization-focused evaluation have the potential to strengthen the quality of RKPD planning if systematically integrated. However, various structural, cultural, and technical barriers hinder the optimal utilization of evaluation results, including a lack of human resource capacity, weak performance information systems, and a low evaluative culture within the regional bureaucracy. This study concludes that the success of annual development planning depends heavily on the extent to which evaluation serves as the basis for developing programs and activities. This study recommends strengthening regulations, digitizing evaluation-planning systems, and building the capacity of civil servants (ASN) to encourage more evidence-based and results-oriented regional development governance.